THE PRINCIPLE OF POLITENESS ACCORDING TO GEOFFREY LEECH IN THE STORY OF THE PROPHET SULAIMAN - Ritonga, Ridwan; Kurniawan, Raden Muhammad Ardansyah (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Language politeness is a code of conduct determined and agreed upon by a particular community, therefore politeness is also an agreed condition in behaving in society. This study discusses the style of Prophet Sulaiman according to Leech's theory. This research uses a descriptive method with a pragmatic approach. The data sources used in this study are divided into two parts, namely primary data sources, namely basic data sources in the form of the Qur'an, and secondary sources, namely books or other sources related to the research topic problem. This study aims to find out the message contained in the story of Prophet Sulaiman a.s in the Qur'an using Geoffrey Leech's approach. The results of this study found that the maxim of wisdom amounted to 2 verses, namely Surah An-Naml verses 20 and 41, the maxim of generosity contained in Surah Shaad verse 32, the maxim of appreciation there were 2 verses, namely in Surah Al-Anbiya verse 81 and An-Naml verse 15, the maxim of simplicity there were 2 verses, namely in Surah An-Naml verses 16 and 36, the maxim of consensus contained in Surah An-Naml verse 38,Â The maxim of sympathy is found in Surah An-Naml verse 19.